Work values and employee commitment in UAE: mediating role of job involvement - Al Marri, Maryam Taresh Saif Suhail (2019)
United Arab Emirates (UAE) is considered as one of the most rapidly developing countries in the Middle East, struggling to be positioned as a service oriented economy. Similar to other parts of the world, the UAE has changed in scope, management and organization. As a result of this pressure, the UAE showed an increased interest in ensuring appropriate work values and job involvement are in place to enhance employee commitment. In this regard, the employee commitment is seen as one of the driving forces behind organizational performance. This study explored the effects of career-growth, social interaction, security and economic, stability and freedom, recreation health and transport as predictors of Ministry of Interior (MOI)’s employee commitment to enhance their effectiveness and efficiency. It was also proposed and analyzed the mediating effect of job involvement through which MOI’s employees being involved in their jobs. The research used a quantitative method through survey instrument and 360 usable questionnaires were collected from the employees in the MOI, UAE. Partial Least Squares (PLS3) was employed to analyze the data. Results showed support for the theoretical model that was studied. The results implied that eight out of eleven direct relationships: career-growth, social interaction, security and economic, stability and freedom, recreation, health and transport, job involvement are related to employee commitment. The mediating effect was also empirically justified, but mediational relationship between security and economic, and employee commitment has confirmed to be statistically negative and not supported. The study has validated theoretical framework and trigger the future research. The results of this research offer a link to its useful applications, the study is also useful and has importance for policy makers, academicians and human resource practitioners to further improving and nurturing employees’ commitment.